On-road NOx emissions of a modern commercial light-duty diesel vehicle using a blend of tyre oil and diesel - Timothy A. Bodisco; S. M. Ashrafur Rahman; Farhad M. Hossain; Richard J. Brown (Energy Reports, 2019)
As a potential means of offsetting diesel fuel usage and reducing the environmental impact of used tyres, this study investigates the NOx emissions of a modern commercial passenger vehicle run on a blend of diesel and tyre pyrolysis oil (TPO). The test vehicle was driven on a route representative of the driving expected by a courier. Vehicle drivability with the TPO/diesel blend, compared to neat diesel, was not reported to be perceived differently by the automotive industry experienced driver. Additionally, the NOx emissions were comparable between the neat diesel trip and those run on the blend of TPO/diesel. Interestingly, the results showed that short transients had a substantive impact on aggregate NOx emissions-making conclusive on-road comparisons between fuels difficult. Despite this, the data collected for this study indicate that there is no substantive NOx emissions degradation when running the TPO/diesel blend.
Keywords: 330; Alternative fuels; Driving dynamics; On-road emissions; Tyre oil